The Evaluation of Electronic Detonators at Martha Mine, New Zealand - Blair Jackson; Tjaart Louw (International Society of Explosives Engineers, 2003)
Martha Mine, owned by Newmont Mining, Australia appointed Macmahon Contractors (NZ) Ltd as the mining contractor to drill, blast, and crush and convey ore for processing, followed by construction of a tails dam facility from the waste material. The open pit is located 140km(90miles) south east of Auckland, New Zealand in the middle of the township of Waihi (the main street of the town with a population of 3,500 is 90m from the perimeter of the open pit mine). Mining must proceed at 325,000m3 (of which involves blasting approximately 11,000 holes per month, in order to ensure continued ore supply.